Applications of complex systems theory in nursing education, research, and practice - Clancy, Thomas R.; Effken, Judith A.; Pesut, Daniel (Nursing Outlook, 2008)
The clinical and administrative processes in today's healthcare environment are becoming increasingly complex. Multiple providers, new technology, competition, and the growing ubiquity of information all contribute to the notion of health care as a complex system. A complex system (CS) is characterized by a highly connected network of entities (e.g., physical objects, people or groups of people) from which higher order behavior emerges. Research in the transdisciplinary field of CS has focused on the use of computational modeling and simulation as a methodology for analyzing CS behavior. The creation of virtual worlds through computer simulation allows researchers to analyze multiple variables simultaneously and begin to understand behaviors that are common regardless of the discipline. The application of CS principles, mediated through computer simulation, informs nursing practice of the benefits and drawbacks of new procedures, protocols and practices before having to actually implement them. The inclusion of new computational tools and their applications in nursing education is also gaining attention. For example, education in CSs and applied computational applications has been endorsed by The Institute of Medicine, the American Organization of Nurse Executives and the American Association of Colleges of Nursing as essential training of nurse leaders. The purpose of this article is to review current research literature regarding CS science within the context of expert practice and implications for the education of nurse leadership roles. The article focuses on 3 broad areas: CS defined, literature review and exemplars from CS research and applications of CS theory in nursing leadership education. The article also highlights the key role nursing informaticists play in integrating emerging computational tools in the analysis of complex nursing systems.